Reduced Reward Responsiveness in Women With Moderate - to - Severe Premenstrual Syndrome: Evidence From a Probabilistic Reward Task - Hou, Lulu; Chang, Lei; Chen, Lirong; Zhou, Renlai (Frontiers in Psychiatry, 2020)
Nearly half of the women of reproductive age worldwide experience premenstrual syndrome (PMS). Women with PMS exhibit low positive affect and low frontal electroencephalography asymmetry scores, both of which are associated with reward processing, suggesting that these women may have deficiencies in reward processing. A probabilistic reward task based on signal detection methodologies was used to assess reward responsiveness in 30 women with moderate-to-severe PMS and 31 controls without PMS. The results revealed that in the late luteal phase, the women with moderate-to-severe PMS exhibited a reduced response bias and a lower hit rate toward more frequently rewarded stimuli (rich stimuli) compared with the women without PMS. By contrast, the response bias and hit rate did not differ between the two groups in the follicular phase. The group differences still remained after controlling for anhedonic symptoms. Furthermore, trial-by-trial probability analyses revealed that women with moderate-to-severe PMS exhibited a trend of having a higher miss rate for rich stimuli. In particular, when a rich trial was preceded by a more infrequently rewarded stimulus (i.e., a rewarded lean trial), the PMS group exhibited a trend for higher miss rate than that of the non-PMS group in both the late luteal and follicular phases. However, the group differences in the probability analyses were nonsignificant after controlling for anhedonic symptoms. These results provide preliminary evidence that women with moderate-to-severe PMS present dysfunctional reward responsiveness and an impaired ability to modulate their behavior as a function of prior reinforcement.